Lumbosacral Transitional Vertebrae in patients attending a Tertiary Care Hospital of Nepal - Khatun, Sanzida; Shah, Diwakar Kumar (Birat Journal of Health Sciences, 2021)
Introduction: Lumbosacral Transitional vertebrae are congenital anomalies of lumbosacral vertebral junction. It may present either as sacralization of fifth lumbar vertebrae or lumbarization of first sacral vertebrae. Various secondary pathological spinal conditions such as intervertebral disc herniation and/or degeneration, facet joint arthrosis and spinal canal or foraminal stenosis are associated with the presence of LSTV. The failure in the identification may lead to clinical consequences such as errors in diagnosis of disease and lumbosacral procedures. Objective: The aim of this study was to determine the prevalence and patterns of LSTV in patients presenting to Department of Radiology of Nobel Medical College Teaching Hospital, Nepal.. Methodology: A descriptive cross-sectional study was conducted in Department of Radiology of Nobel Medical College Teaching Hospital, Nepal.Plain radiographs including Antero-posterior (AP) and Lateral views of lumbosacral spine of 343 patients referred for the scan were analyzed for the presence of lumbosacral vertebrae. Result: Out of 343 patients, LSTV was found in 61 (17.8%) subjects. Thirty-eight subjects (11.1%) exhibited sacralization and 23 (6.7%) showed lumbarization.Out of total LSTV subjects, type I A was present in 8 (13.1%), type I B in 21 (34.4%), type II A in 10 (16.4%), type II B in 5 (8.2%) , type III A in 6 (9.8%) , type III B in 9 (14.8%) and type IV in 2 (3.3%). Conclusion: The LSTV is prevalent in almostone-fifth of subjects presenting to department of radiology of Nobel Medical College and Teaching Hospital, Biratnagar for lumbosacral scan.. Sacralization occurs more frequently than lumbarization, both of which alter the morphology of anatomical structures in spine. The presence of anomaly in this region may be related to occurrence of various pathological and clinical conditions.